2016
DOI: 10.1120/jacmp.v17i3.6059
|View full text |Cite
|
Sign up to set email alerts
|

Small field detector correction factors: effects of the flattening filter for Elekta and Varian linear accelerators

Abstract: Flattening filter‐free (FFF) beams are becoming the preferred beam type for stereotactic radiosurgery (SRS) and stereotactic ablative radiation therapy (SABR), as they enable an increase in dose rate and a decrease in treatment time. This work assesses the effects of the flattening filter on small field output factors for 6 MV beams generated by both Elekta and Varian linear accelerators, and determines differences between detector response in flattened (FF) and FFF beams. Relative output factors were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…This is exacerbated by the removal of the flattening filter from the LINAC, which results in most of the low-energy photons to pass through and a consequent lower average beam energy 6 . As previously reported, though, deviations in small fields correction factors for silicon diodes between flattened and FFF beams are sufficiently small (up to a maximum of ± 1.7%) to allow for their potential interchangeability on the same LINAC 27 . Consistently with this result, we used the same air gap to render the Octa a 'correction-free' dosimeter for OFs measurements for all beam qualities investigated.…”
Section: Output Factorssupporting
confidence: 58%
“…This is exacerbated by the removal of the flattening filter from the LINAC, which results in most of the low-energy photons to pass through and a consequent lower average beam energy 6 . As previously reported, though, deviations in small fields correction factors for silicon diodes between flattened and FFF beams are sufficiently small (up to a maximum of ± 1.7%) to allow for their potential interchangeability on the same LINAC 27 . Consistently with this result, we used the same air gap to render the Octa a 'correction-free' dosimeter for OFs measurements for all beam qualities investigated.…”
Section: Output Factorssupporting
confidence: 58%
“…1 The IAEA TRS-483 CoP for small field dosimetry recommends detectors used for QA should be: small relative to the minimum field size and the range of the secondary charged particles, have a high signal to noise ratio (SNR), high spatial resolution and also be energy, dose rate, and angular independent in response. Volume averaging effects can be avoided by the use of detectors with submillimeter spatial resolution, such as the PTW microDiamond, [2][3][4][5] IBA razor diode detector, 6 and the edgeless silicon diode, 7 however, these detectors do not address some of the more serious perturbation effects. A tissue equivalent, small volume detector can be made for plastic scintillators but these detectors suffer from a large temperature and humidity dependence as well as nonlinearity at low doses.…”
Section: Introductionmentioning
confidence: 99%
“…This near water equivalent detector has a minimal sensitive volume of 0.0004 cc and is a good candidate for small-field dosimetry. Study has shown that this detector has minimal energy, temperature, and directional dependency; thus changes within these factors will not influence the measured signal [14].…”
Section: Introductionmentioning
confidence: 99%